Guidance on farmer participation in the design, testing and scaling of agricultural innovations - Pawera, Lukas; Manickam, Ravishankar; Wangungu, Carolyne; Bonnarith, Uon; Schreinemachers, Pepijn; Ramasamy, Srinivasan (Elsevier, 2024)
Despite accelerated developments in agricultural innovations, there has been a limited progress in their adoption by smallholder farmers, especially in the Global South. Innovations are not adequately reaching farmers, and new technologies are often unsuitable for farmers, or the overall innovation landscape is discouraging the deployment of innovations at scale. The methodological approaches to designing, testing and scaling of innovations play an important role. Involving farmers in the innovation process from the start increases the likelihood of them being more relevant and having a higher chance of adoption. Whereas there is much literature on participatory approaches, there is a limited guidance on choosing an appropriate level of farmer participation across the innovation process.